USULAN PERBAIKAN PADA PROSES BONGKAR MUAT PETIKEMAS DENGAN PENDEKATAN LEAN - Mega Nilam Sari, (2021)
PT. K is the ports that provides container loading and unloading services. To ensure the container flows, PT K has an operational performance standards to carrying out the loading and unloading process. One of the indicators is the effective time ratio. The effective time ratio that does not reach the standards is influenced by the length of service time for loading and unloading activities. This is caused by waste activities in the process while the ship is at the mooring. This study aims to identify waste and provide a proposed improvement plan to reduce waste that occurs using a lean approach. The method used is a questionnaire of seven waste, BPM, VALSAT, FTA and HOR. Calculation results based on the seven waste questionnaire, it was found the most dominant waste, that is waste of waiting with an average value of 3.6, waste of transportation with an average value of 3.4, waste of inventory with an average value of 3.2 and defects with an average value of 2.8. Based on the FTA analysis, it was found that the waste caused by slow docking process, unprepared workers, troubled and congestion in the field. Based on the HOR analysis, it was found that a proposed improvement plan in the form of a strategy for handling the highest causes of waste, there are carrying out equipment maintenance, making a maintenance report cards, conducting work evaluation meetings, strengthening internet connections and adding RTG and QCC units.